O perfil e o desempenho ocupacional de crianças com doença renal crônica - SANTOS, Heloisa Sâmella Santos dos (2023)
Introduction: Chronic Renal Disease (CKD) is little discussed, but it has been an increasing object of attention by the Brazilian health system. Currently, children do not represent a significant number of people living with CKD, but represent a challenging audience with regard to health interventions especially for Occupational Therapy professionals who are not backed by public policies to make up the minimum care staff in the care line to the person with CKD. Objectives: To investigate the profile and occupational performance of children with chronic renal disease (CKD) in hemodialysis treatment and repercussions on family routine. Methodology: This is an exploratory, descriptive study with a qualitative approach, using two semi structured interviews and the Occupational Performance Measure (COPM). Results: The main areas of occupational performance related to the activities of bathing alone, playing ball, traveling and swimming in the pool were identified. The study also showed the occupational profile of the children taking into account the most outstanding occupations by the participants, shown in three categories: self care, play and education. Changes were observed in the family routine, where the days with the hemodialysis routine and the days without the treatment were evidenced, besides the changes in the routine of the main caregiver. Final considerations: This study is of great relevance in that it deals with a topic not explored by occupational therapists and once the occupational repercussions of CKD on the child undergoing hemodialysis and the family routine are known, there may be advances in interventions and attitudes that will favor humanized and systematized support for these children.